Early left atrial dysfunction is associated with suboptimal cardiovascular health. Issue 1 (18th December 2019) - Ocaranza, María Paz; Bambs, Claudia; Salinas, Manuel; Matamala, Cristian; Garcia, Lorena; Troncoso, Rodrigo; Pedrozo, Zully; Huidobro, Andrea; Venegas, Pia; Paredes, Fabio; Giacaman, Arturo; Zalaquett, Ricardo; et al.
Abstract: Aims: Two‐dimensional speckle‐tracking echocardiography can assess left atrial (LA) function by measuring atrial volumes and deformation parameters (strain, strain rate). This cross‐sectional analysis explores the association between ideal CV health (CVH), LA function, and systemic biomarkers in healthy individuals from the Chilean MAUCO Cohort. Methods: We enrolled 95 MAUCO participants with different levels of CVH (mean age: 51 ± 8 years). We categorized participants into low or high CVH groups: A: 0‐2, or B: 3‐6 CVH risk factors. 2D echocardiography, glucose, insulin, total cholesterol, triglycerides, proBNP, hsCRP, insulin resistance index (HOMA), and right and left atrial strain (RASs and LASs, respectively) were determined. Results: LASs was lower in Group A, while systolic and diastolic blood pressure (BP), body mass index (BMI), insulin, HOMA, total cholesterol, triglycerides, and LV and RV end‐diastolic volume were significantly higher in Group A than Group B ( P < .01). Change in LASs was inversely correlated with insulin ( P = .040), HOMA ( P = .013), total cholesterol ( P = .039), glycemia ( P = .018), and BMI ( P = .0.037). Conclusion: LASs during the reservoir phase was diminished in subjects with a lower level of CVH. Higher insulin, HOMA, total cholesterol, glycemia, and BMI values were associated with decreased LA deformation during the reservoir phase. Morphofunctional alterations of the LA were also identified in the group with suboptimal CVH, as well as BP values in the range of hypertension. LA dysfunction in an asymptomatic population, along with metabolic syndrome, could be an early event in the continuum of CV damage.